Influence Of pH on Biogas Production from Organic Waste at High Voltage Pulse Current - N.Imomova, X.Muratov, А.Хudoyberdiyev, R.Rozikov (Zien Journals, 2022)
Providing the used biogas devices with regulators at the level of the anaerobic process demand, preventing anaerobiosis occurring in them, preventing the mixing of newly added biomass with organic fertilizer being processed, keeping the amount generated by organic waste sources in proportion to the amount of daily loading into the bioreactor, and the amount of biogas and fertilizer obtained information is given on the issues of ensuring that the quality does not decrease
Keywords: biogas, temperature, bioreactor, regulator, drum, biomass, biowaste